Application of Fourier transform infrared spectroscopy on Breast cancer diagnosis combined with multiple algorithms: A systematic review - Yeniewa Kerie Anagaw; Gizachew Kassahun Bizuneh; Melaku Getahun Feleke; Liknaw Workie Limenh; Derso Teju Geremew; Minichil Chanie Worku; Melese Legesse Mitku; Misganaw Gashaw Dessie; Biset Asrade Mekonnen; Wondim Ayenew (Photodiagnosis and Photodynamic Therapy)
Introduction: Fourier transform infrared (FT-IR) spectroscopy is an innovative diagnostic technique for improving early detection and personalized care for breast cancer patients. It allows rapid and accurate analysis of biological samples. Therefore, the purpose of this study was to assess the diagnostic accuracy of FT-IR spectroscopy for breast cancer, based on a comprehensive literature review. Methods: An online electronic database systematic search was conducted using PubMed/Medline, Cochrane Library, and hand databases from March 28, 2024, to April 10, 2024. We included peer-reviewed journal articles in which FT-IR spectroscopy was used to acquire data on breast cancers and manuscripts published in English. All eligible studies were assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) tool. Results: Serum, breast biopsies, blood plasma, specimen, and saliva samples were included in this study. This study revealed that breast cancer diagnosis using FT-IR spectroscopy with diagnostic algorithms had a sensitivity and specificity of approximately 98 % and 100 %, respectively. Almost all studies have used more than one algorithm to analyze spectral data. This finding showed that the sensitivity of FT-IR spectroscopy reported in six included studies was greater than 90 %. Conclusion: Employing multivariate analysis coupled with FT-IR spectroscopy has shown promise in differentiating between healthy and cancerous breast tissue. This review revealed that FT-IR spectroscopy will be the next gold standard for breast cancer diagnosis. However, to draw definitive conclusions, larger-scale studies, external validation, real-world clinical trials, legislative considerations, and alternative methods such as Raman spectroscopy should be considered.